Balancing the trade-off between measurement uncertainty and measurement time in optical metrology using design of experiments, meta-modelling and convex programming. (November 2021) - Gauder, Daniel; Gölz, Johannes; Biehler, Michael; Diener, Moritz; Lanza, Gisela
Abstract: Micro gears represent key components in an increasing number of industry, applications. To satisfy the increasing quality requirements in terms of lifetime and noise emissions, new function oriented measurement strategies need to be implemented, that allow the deployment of Inline Quality Control Cycles. Therefore, a Design of Experiments (DoE) is conducted and the measurement uncertainty systematically evaluated in accordance to Guide to the Expression of Uncertainty of Measurement (GUM). Furthermore, this paper describes a method to optimize the tradeoff between measurement uncertainty and measurement time in optical metrology with a use case in micro gear measurement using focus variation. This optimization method uses a meta-model and hyperparameters to allow the adjustment to specific operating conditions and use cases.